Personal Income Tax Compliance Behaviour in Kathmandu Valley - Toya Nath Bhattarai (Pravaha, 2023)
This article aimed to explore whether factors such as tax awareness and knowledge, the perceived fairness of the tax system, its complexity, tax rates, and income levels influence the compliance behavior of registered personal income taxpayers in the Kathmandu Valley. A theoretical framework was employed to test hypotheses based on responses gathered from a survey of these taxpayers. Data collection was carried out using a purposive judgmental sampling method, and questionnaires were distributed as part of a descriptive and analytical research design. The collected data were analyzed using least squares regression and SPSS 26.0. The results indicated that personal income tax compliance, the dependent variable, was significantly and positively influenced by five key factors: tax awareness and knowledge, fairness of the tax system, complexity of the tax system, tax rates, and income level. The findings also revealed that taxpayers often lack sufficient technical knowledge and perceive the tax system as overly complex. These factors—along with tax awareness, fairness, complexity, tax rates, and income level—are thought to contribute to taxpayer non-compliance. To enhance tax compliance, the study recommends that the government should focus on improving public services, increasing awareness about the benefits of paying taxes, and educating the public on compliance measures. Additionally, conducting regular audits can act as a deterrent to non-compliance. Future research could investigate the impact of social and referral groups on compliance behavior, as social norms and ethical values may offer further incentives for tax compliance.